1992
DOI: 10.30541/v31i1pp.31-48
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Characteristics and Household Savings: An Analysis of the Households' Saving Behaviour in Pakistan

Abstract: Domestic resource mobilization is one of the key determinants of sustained economic growth. Pakistan's perfonnance with regard to domestic resource mobilization has been poor despite maintaining a respectable economic growth rate. Why is the savings rate so low in Pakistan? In this paper we analyse the household savings behaviour in Pakistan, using micro level data of the Household Income and Expenditure Survey (HIES) for the year 1984-85. Three different non-linear savings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 16 publications
6
38
0
3
Order By: Relevance
“…A positive and statistically significant coefficient of 1 in Equation (8) and 1 in Equation (9) would support the traditional Keynesian wisdom that equalization of income distribution increases aggregate consumption (Burney and Khan, 1992). In order to test the hypothesis of linear versus nonlinear relationship between savings and income, Landau (1971) suggested the functional form of Eq.…”
Section: = −mentioning
confidence: 95%
See 1 more Smart Citation
“…A positive and statistically significant coefficient of 1 in Equation (8) and 1 in Equation (9) would support the traditional Keynesian wisdom that equalization of income distribution increases aggregate consumption (Burney and Khan, 1992). In order to test the hypothesis of linear versus nonlinear relationship between savings and income, Landau (1971) suggested the functional form of Eq.…”
Section: = −mentioning
confidence: 95%
“…However, the possibility of encountering problems with heteroscedasticity of the estimates of the coefficients of 1 , 2 and 3 make Equation (7) equally unsuitable. One way according to Burney and Khan (1992), to avoid the problem of heteroscedasticity is to express savings as a percentage of income as given by Eq. 8.…”
Section: = −mentioning
confidence: 99%
“…In micro level data based studies, age, education, income, household size, gender, location are used as a standard set of observable variables in order to determine the effect of heterogeneity of household on savings Burney and Khan (1992) Gibson and Scobie (2001), Guariglia and Kim (2004), Foley and Pyle (2005), Orbeta (2006), Szekely and Attanasio (2000), Chamon and Prasad (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The saving rate, however, continues to show an almost horizontal trend over the years [Pakistan (2006); State Bank (2006)]. Household income has been found to be the prime factor influencing saving behaviour in Pakistan and various studies found a strong inverse relation between dependency ratio and savings in the country [Ahmed and Asghar (2004); Khan and Nasir (1999); Burney and Khan (1992); Siddique and Siddique (1993);and Khan, Hasan, and Malik (1992)]. …”
Section: Savingsmentioning
confidence: 99%